Potential Conflict and the Absence of Effective Conflict Resolution Mechanisms: The Case Of Bondowoso Village Election - Bahar, Moh Syaeful (UIN Sunan Ampel Surabaya, 2024)
This study examines the dynamics and potential sources of conflict emerging from the Village Head Election (Pilkades) in Grujugan Kidul Village, Bondowoso Regency, Eas Java. Following the decentralization era, village democracy has provided wider participation opportunities for local communities; however, electoral competition at the village level often generates social tensions due to strong emotional ties and close social relations among villagers. The research aims to identify conflict potentials, analyze conflict patterns, and evaluate the effectiveness of conflict resolution mechanisms within village political processes. This research employs a qualitative participatory approach to obtain a holistic understanding of social realities surrounding Pilkades. Data were collected through participatory observation, in-depth interviews with nineteen informants selected through snowball sampling, and literature review. Conflict theory perspectives were applied as the analytical framework to interpret social interactions, elite dynamics, and patterns of political contestation occurring before, during, and after the election process. The findings reveal that conflict originated from limited public understanding of democratic values and competition, resulting in emotional rather than rational political support. Such conditions encouraged blind fanaticism among supporters and intensified polarization within the community. Conflict developed through three stages: latent conflict before the election, manifest conflict during the election, and complex post-election conflict involving community groups and local government institutions. The study also finds that conflict resolution mechanisms were ineffective due to persistent elite tensions and the weakened mediating role of religious leaders. Consequently, latent social disharmony continued to shape community relations even after the electoral process ended.